Strategi Public Relations Teh Villa Dalam Meningkatkan Citra Perusahaan - Dyva Claretta; Ester Permata Putri; Lina Yuniati; Ika Rahmawati (CV. ITTC INDONESIA, 2022)
Indonesia is a country with a tropical climate and there are several areas in Indonesia with cool temperatures. With these advantages, many types of plants grow, such as tea, which can be processed into food. One of the most mushrooming food products in Indonesia is tea. The plurality of tea companies in Indonesia, every tea product brand in Indonesia has its own image that is remembered by consumers. The image is built through various public relations programs within the company. Each program that is run has a goal by targeting a predetermined segmentation. To launch the program, a PR must determine a PR strategy that suits the public. As done by the Tea Villa PT. Mas Makmur's work using a special event exhibition in collaboration with several artists in Indonesia. Then the proceeds from the exhibition were used for CSR programs and donated to orphanages.